Hak Recall Partai Politik Terhadap Anggota Dewan Perwakilan Rakyat: Tinjauan Constituent Dan Public Recall - Muhammad Mutawalli; Mukhtar Lutfi; Mau Lulo, Lourenco de Deus; Lohalo, Georges Olemanu (Universitas Medan Area, 2023)
Therefore, the idea of constituent and public recall is the basis for the manifestation of people's involvement, in whose position the people are subjects who have the will of constituents and are a public element in determining the survival of the people. representatives who represent them. This paper is qualitative research using normative juridical methods. In this paper, a legislative approach, a conceptual approach, and a philosophical approach are used. This research was carried out by tracing legal materials through law books, books, scientific works, and even several printed media that are useful and relevant to this article. The collected material is then processed and analyzed in depth, then presented in a qualitative descriptive and analytical prescriptive manner. The conclusion of this paper shows that political parties have the authority to recall (replace) legislative members as part of their overall authority. The concepts of constituent recall and public recall are needed so that political parties have the right to replace members of the People's Representative Council because this highlights the importance of involving the community as holders of the people's sovereign rights in the mechanism for dismissing council members. Once elected, legislative members can be dismissed, but this is not ideal and participatory and seems feudal because it is still determined by the will of the party elite, even though the principle of popular sovereignty which must be prioritized is weakened by power. There are no regulations regarding constituent and public recall mechanisms.